THE ROLE OF GIS AND REMOTE SENSING TECHNOLOGIES IN PREVENTING SOIL EROSION IN IRRIGATED AREAS (The Conference Hub, 2025)
This article analyzes the scientific basis and practical application of geographic information systems (GIS) and remote sensing (RS) technologies in preventing soil erosion in irrigated lands. Soil erosion is an important factor threatening the stability of agroecosystems, especially strongly manifested in irrigated areas of arid regions. With the help of remote monitoring methods, risk zones are identified by observing changes in vegetation, relief, and salinity at the earth's surface. On GIS platforms, the amount of soil loss is assessed by mathematical calculations using models such as USLE/RUSLE. The article highlights analytical results in real areas based on scientific and practical research conducted in Iran, Morocco, and Uzbekistan. The effectiveness of erosion monitoring and control measures using spectral indices (NDVI, NDSI), UAV images, and AI algorithms is also highlighted. Based on the results, it is proposed to form an integrated monitoring system with contour planting, drip irrigation, terracing, and other measures.